Contemplation An Islamic Psychospiritual Study - Badri, Malik (International Institute of Islamic Thought, 2000)
The human race is in crisis and very few of us if any are able to understand what is wrong with our lives and the world at large. How did this happen and how did humans become so 'disconnected' with humanity? Why are psychological disorders such as depression, anxiety, fear, and suicide on the increase, and why are conventional Western therapies unable to stem the tide? To approach this, we must first look inside ourselves to explore our own purpose in life and extend that principle to the rest of humanity. Despite the advances of modern Western psychology and the development of therapies that do help many, one area that is largely unexplored is that of the 'human spirit' and spirituality since it is more convenient to consider the human mind as 'machine' that responds to external stimuli. In this powerful exploration into the human mind and its relationship with the human spirit, Malik Badri invites the reader to open the door to selfdiscovery, purpose and spirituality through the practice of contemplation, reflection and meditation understanding the true meaning and experience of spirituality as well as one's own place in Creation. Whilst central to worship in Islam, this will also be of great interest to, and help any reader wishing to explore the notion of spirituality whether as part of worship or simply as part of self-development and inner healing.